A Case of Infective Endocarditis and Pulmonary Septic Emboli Caused by Lactococcus lactis. (27th September 2016) - Mansour, Bshara; Habib, Adib; Asli, Nazih; Geffen, Yuval; Miron, Dan; Elias, Nael
Abstract : Infective endocarditis is a rare condition in children with normal hearts. We present here a case of previously healthy eleven-year-old girl with infective endocarditis and pulmonary septic emboli caused by a very rare bacterial etiology ( Lactococcus lactis ). Identification of this pathogen was only made by polymerase chain reaction.